2021
DOI: 10.3762/bjoc.17.85
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of multiply fluorinated N-acetyl-D-glucosamine and D-galactosamine analogs via the corresponding deoxyfluorinated glucosazide and galactosazide phenyl thioglycosides

Abstract: Multiple fluorination of glycostructures has emerged as an attractive way of modulating their protein affinity, metabolic stability, and lipophilicity. Here we described the synthesis of a series of mono-, di- and trifluorinated N-acetyl-ᴅ-glucosamine and ᴅ-galactosamine analogs. The key intermediates are the corresponding multiply fluorinated glucosazide and galactosazide thioglycosides prepared from deoxyfluorinated 1,6-anhydro-2-azido-β-ᴅ-hexopyranose precursors by ring-opening reaction with phenyl trimethy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…There are no dedicated syntheses of 1,3-difluorinated aminosugars, but it is worth mentioning observations by the Karban group regarding a 1 → 6 migration process when deoxyfluorinating the 6-position of β-configured thioglycosides (Scheme 128). 429 This process, originally described with a 2-O-benzoylated β-configured methyl galactoside, 145 had been expanded by the Lin group (with β-thiophenolates), where they showed that high yields of migration can be achieved, for example in the conversion of 895 to 896 (Scheme 128A). 430 Upon treatment of a mixture of anomers 897 (Scheme 128B, see below Scheme 139 for their synthesis), the Karban group isolated four products, 429 with α-898 arising from clean deoxyfluorination of the α-anomer of 897, while β-898, α-899, and β-899 arose from the β-anomer of 897.…”
Section: Fluorination At Positions 1 Andmentioning
confidence: 99%
See 4 more Smart Citations
“…There are no dedicated syntheses of 1,3-difluorinated aminosugars, but it is worth mentioning observations by the Karban group regarding a 1 → 6 migration process when deoxyfluorinating the 6-position of β-configured thioglycosides (Scheme 128). 429 This process, originally described with a 2-O-benzoylated β-configured methyl galactoside, 145 had been expanded by the Lin group (with β-thiophenolates), where they showed that high yields of migration can be achieved, for example in the conversion of 895 to 896 (Scheme 128A). 430 Upon treatment of a mixture of anomers 897 (Scheme 128B, see below Scheme 139 for their synthesis), the Karban group isolated four products, 429 with α-898 arising from clean deoxyfluorination of the α-anomer of 897, while β-898, α-899, and β-899 arose from the β-anomer of 897.…”
Section: Fluorination At Positions 1 Andmentioning
confidence: 99%
“…429 This process, originally described with a 2-O-benzoylated β-configured methyl galactoside, 145 had been expanded by the Lin group (with β-thiophenolates), where they showed that high yields of migration can be achieved, for example in the conversion of 895 to 896 (Scheme 128A). 430 Upon treatment of a mixture of anomers 897 (Scheme 128B, see below Scheme 139 for their synthesis), the Karban group isolated four products, 429 with α-898 arising from clean deoxyfluorination of the α-anomer of 897, while β-898, α-899, and β-899 arose from the β-anomer of 897. The major product was the migration product α-899.…”
Section: Fluorination At Positions 1 Andmentioning
confidence: 99%
See 3 more Smart Citations